Notes on relative and correlative constructions in Gǝʿǝz - Kapeliuk, Olga (Aethiopica, 2003)
ዘሞትነ ንሕነ ወዘነገሥነ ንሕነ: The relative verb accompanied by its headnoun, forming a relative clause which functions as the equivalent of an adjective, is the normal construction in the Semitic languages. In Gǝʿǝz, however, it is the substantivized relative clause, in which the headnoun is missing, that is the most diversified in its function and probably statistically more frequent. These are the correlative clauses. They present some specific morpho-syntactic features; thus the feminine relative pronoun is not encountered in them and the number of the relative pronoun is consistently accorded with the putative headnoun. In the regular relative clauses the headnoun is a noun or an independent pronoun but also suffixed pronouns and whole sentences may be qualified by a relative clause. Nominal sentences are common as relative or correlative clauses. In case the predicate of the nominal clause is a substantive, a pronoun with copulative function is introduced preventing the confusion between the construction in question and a possessive complex with nota genetivi.